2008
DOI: 10.1002/cbdv.200890083
|View full text |Cite
|
Sign up to set email alerts
|

Marine Fragrance Chemistry

Abstract: The main marine message in perfumery is projected by Calone 1951 (7-methyl-2H-1,5-benzodioxepin-3(4H)-one). Kraft (Givaudan) and Gaudin (Firmenich) further maximized the marine fragrance molecular membership by extending the carbon chain of the 7-Me group. Our research targeted the polar group of the benzodioxepinone parent compound to investigate how this region of molecular makeup resonates with the dominant marine fragrance of the Calone 1951 structure. The olfactory evaluation of analogues prepared by chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Macrocyclic benzolactones such as the marine salicylihalamides and structurally related salicylic acid lactones exhibit attractive biological properties; also, the lichen and endophytic fungi-derived class of depsidones with their characteristic seven-membered benzo[ e ]1,4-dioxepan-5-one core shows a broad range of interesting biological activities . Moreover, in perfumery, so-called marine notes mainly stem from benzodioxepinone compounds …”
mentioning
confidence: 99%
“…Macrocyclic benzolactones such as the marine salicylihalamides and structurally related salicylic acid lactones exhibit attractive biological properties; also, the lichen and endophytic fungi-derived class of depsidones with their characteristic seven-membered benzo[ e ]1,4-dioxepan-5-one core shows a broad range of interesting biological activities . Moreover, in perfumery, so-called marine notes mainly stem from benzodioxepinone compounds …”
mentioning
confidence: 99%
“…The most famous was Calone or 7-methyl-2H-1,5-benzodioxepin-3(4H)-one (2a), trade-named Calone 1951, also known in the industry as "watermelon ketone" with a very low odor threshold of 3.1 × 10 −2 ng/L air [190]. It was undeniably the starting point of the history of synthetic molecules reflecting the marine environment, which revolutionized perfumes of marine origin and was responsible for defining an entire genus [191][192][193]. Consequently, for 30 years , Calone 1951 ® (3) was the only commercialized compound in this series (Figure 2), it was particularly popular in the 1990s.…”
Section: Marine Fragrance Chemistrymentioning
confidence: 99%
“…[221] Certain functional groups and chemical structural arrangements might confer some anticipated aroma activity to the compound, which is expected given that a structure-activity relationship also relates to the nasal receptors based on biological shape. For instance, the 'sea breeze / marine odour' range of compounds patented by Givaudan ('Calone 1951') had a common benzodioxepinone active site, and variants were synthesised by extending the 7-methyl carbon chain [222], whilst still ensuring adequate volatility. But a most important aspect of olfactometry studies is that notwithstanding the different aromas that might be reported, it is important to provide identification of the responsible molecules which might be very difficult for exceedingly low concentration compounds of high activity.…”
Section: Applications Of Gc-ncdmentioning
confidence: 99%